2014
DOI: 10.1186/1824-7288-40-44
|View full text |Cite
|
Sign up to set email alerts
|

Parenting approaches and digital technology use of preschool age children in a Chinese community

Abstract: BackgroundYoung children are using digital technology (DT) devices anytime and anywhere, especially with the invention of smart phones and the replacement of desktop computers with digital tablets. Although research has shown that parents play an important role in fostering and supporting preschoolers’ developing maturity and decisions about DT use, and in protecting them from potential risk due to excessive DT exposure, there have been limited studies conducted in Hong Kong focusing on parent-child DT use. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
100
1
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 37 publications
14
100
1
17
Order By: Relevance
“…As positive effect, it can develop positive attitude towards learning, improve reading skills and visual intelligence, develop psychomotor skills, and contribute to language learning (Li, Atkins & Stanton, 2006; Jackson et al, 2011). As negative effect, it increase the risks of obesity and musculoskeletal problems (Bremer, 2005), it can develop addictive disorders and aggressive behavior (Subrahmanyam et al, 2000;Wu et al, 2014), and it can lead to social isolation (Jackson et al, 2011). Taking in consideration these positive and negative effects, the attitude towards using computers in early childhood is very variant among teachers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As positive effect, it can develop positive attitude towards learning, improve reading skills and visual intelligence, develop psychomotor skills, and contribute to language learning (Li, Atkins & Stanton, 2006; Jackson et al, 2011). As negative effect, it increase the risks of obesity and musculoskeletal problems (Bremer, 2005), it can develop addictive disorders and aggressive behavior (Subrahmanyam et al, 2000;Wu et al, 2014), and it can lead to social isolation (Jackson et al, 2011). Taking in consideration these positive and negative effects, the attitude towards using computers in early childhood is very variant among teachers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Small children develop new skills in digital technology use through observing their parents. Thus, it can be inferred that healthy behavior models play a critical role in safe use of these tools by children (Wu et al, 2014). In a study by Funk, Brouwer, Curtiss and McBroom (2009), it was found that parents' guidance in digital technology use was inadequate, which had negative effects on children.…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Plowman, McPake and Stephen (2010), risky situations in children's digital technology use were revealed, but parents stated that they did not worry about their children's digital technology use as they believed that they had taken the necessary precautions. In a study aiming to determine children's digital technology use and parents' opinions about this topic, families were found to adopt a restrictive attitude towards the use of such technologies, which could be due to parents' desire to protect children from inappropriate media content and other risks (Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations